Influence of Exercise and Intra-articular Site on Canals in Articular Calcified Cartilage of Equine Third Carpal Bones. (May 2016) - Herdan, C. L.; Nicholson, C. L.; Firth, E. C.
The third carpal bone (C3) responds to exercise by adaptive modeling of bone and articular calcified cartilage along the dorsal load path. Canals penetrating articular calcified cartilage, thought to contain vascular tissue, are reported in numerous species. Their significance remains unclear. Our objective was to determine if the number of canals was significantly different in strenuously exercised and control young horses and in a site of intermittent high loading compared to sites sustaining lower habitual loads. Volumetric bone mineral density in the radial facet of C3 of strenuously exercised and gently exercised (control) 19-month-old thoroughbred horses ( n = 6/group) was determined by peripheral quantitative computed tomography. The hyaline cartilage was corroded to expose the surface of articular calcified cartilage. The number of canals penetrating the articular calcified cartilage surface in en face scanning electron microscopy images was compared in 4 regions. Volumetric bone mineral density of C3 was significantly greater ( P = .004) in strenuously exercised horses. There were 2 morphologically distinct groups of canals and significantly fewer ( P = .006) large canals in the dorsal than in the palmar aspect of C3 in control but not in exercised horses. Roughly circular depressions in the articular calcified cartilage surface around apparently forming canals were visible in some samples and have not been previously described in the literature. The canals may be evidence of chondroclastic activity reaching the interface of hyaline and calcified cartilage. Further work is needed to elucidate the relationships between presence of canals and the responses to exercise and to joint disease.